A positive plate for high-rate, long-cycle, high-safety lithium battery and a preparation method and application thereof
Patent Information
- Application Number
- CN202210113787.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-30
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-01-30
AI Technical Summary
缺点:方法工艺复杂,影响电池倍率性能
本发明的锂电池正极片中加入的第一组分和第二组分的混合组分颗粒化学稳定性高,可以在正极片制备前直接掺混在正极活性材料当中,不改变当前正极片、隔膜和电池的主流制备工艺,与现有锂离子电池正极片的主流制备工艺相兼容,不影响正极和电芯的制备工艺,具有稳定性高、成本低的优势,适合大规模应用。相比之下,正极材料掺杂或正极表面包覆的方法都需要改变现有正极材料制备技术,难以同时提高放电比容量和倍率性能。
Smart Images

Figure CN116565202B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, and in particular to a positive electrode sheet for high-rate, long-cycle, and high-safety lithium batteries, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries have advantages such as high energy density, good cycle performance, long service life, low self-discharge, and no memory effect. They are gradually occupying a larger application market in energy storage, power batteries, and 3C electronics, and have broad application prospects.
[0003] Lithium-ion batteries are continuously being developed towards higher energy density to provide better range for electric vehicles, digital products, and other power electronic devices. Increasing the loading and compaction density of electrode plates, especially the positive electrode plate, is an effective way to improve battery energy density. However, as the loading and compaction density of the positive electrode plate increase, the active material layer thickens and the porosity decreases, making lithium-ion transport within the positive electrode plate difficult. This leads to severe battery polarization, a decrease in the battery's discharge specific capacity and rate performance, and a reduction in cycle stability. Simultaneously, as battery energy density increases, battery safety often becomes more difficult to guarantee. To date, no technology can simultaneously solve all of these problems.
[0004] Existing methods for improving battery rate performance include: Cathode surface doping: Patent application CN113224287A discloses a strontium-doped ternary lithium-ion battery cathode material (Li). 1-x Sr x [Ni 1-y-z Co y M z [O2, where M is one of metals Mn and Al, 0 < x ≤ 0.1, 0 < y ≤ 1, 0 < z ≤ 1) and its preparation method and applications. By doping lithium sites with strontium metal ions, the degree of cation mixing is reduced, lithium ion channels are expanded, and the layered structure is stabilized, effectively improving the rate performance of lithium batteries. However, while this method improves rate performance, it often leads to accelerated capacity decay.
[0005] Existing methods for improving battery safety performance include: Cathode Coating: Patent application CN113809280A discloses a cathode material and its preparation and application. By modifying the sintering technique and utilizing the interaction between the coating agent, a cathode material with a near-planar coating effect is prepared. The cathode material prepared by this method has a large surface coating coverage, significantly reducing the erosion of material particles by the electrolyte, effectively reducing the probability of side reactions, and thus improving material safety. Disadvantages: The method is complex and affects battery rate performance.
[0006] Existing methods for simultaneously improving battery electrical performance and safety performance: CN 108365260 B discloses a quasi-solid-state electrolyte, the raw material composition of which includes a polymer, a ceramic electrolyte, a lithium salt, and an ionic liquid. The ceramic electrolyte comprises a main phase of lithium aluminum titanium phosphate and a heterogeneous phase of TiP2O7 / TiO2. Preferably, the heterogeneous phase content in the ceramic electrolyte is 2-7%, and the mass ratio of TiP2O7 to TiO2 is 1.5-2.5:1. The quasi-solid-state electrolyte prepared from the ceramic electrolyte with this heterogeneous phase content exhibits the best overall performance. The heterogeneous phase with this specific composition and content possesses lithium storage characteristics, which can improve lithium-ion transport performance and reduce the contact between the main phase of lithium aluminum titanium phosphate and metallic lithium, thereby improving the interfacial stability with metallic lithium. However, this patent does not improve the positive electrode's electrical performance and safety performance, and the method is incompatible with the mainstream preparation process of existing lithium-ion battery positive electrodes, making it unsuitable for large-scale applications.
[0007] CN113707880A relates to a positive electrode containing a solid electrolyte, its preparation method, and its application, aiming to improve the rate performance, cycle performance, and safety performance of batteries. The solid electrolyte in the positive electrode slurry facilitates the transverse and longitudinal transport and wetting of the electrolyte within the electrode, aiding in electrolyte storage and wetting. During cell cycling, it also helps alleviate electrode expansion, reducing the amount of electrolyte squeezed out under pressure, ensuring sufficient electrolyte within the electrode even after long-term cycling, thus guaranteeing normal lithium-ion transport and improving cycle performance. However, data from the embodiments show only a slight improvement in battery capacity and safety, with insufficient data to support the effect on rate performance. This indicates that adding conventional solid electrolytes cannot comprehensively improve battery electrical and safety performance.
[0008] CN113346066B discloses a polymetallic phosphate-coated lithium cobalt oxide cathode material and its preparation method. The invention suggests that the polymetallic phosphate coating layer on the surface of the lithium cobalt oxide cathode material matrix is a fast ion conductor, which can improve the material's rate performance. The coating layer can also prevent reactions between the electrode and the electrolyte, slowing down the capacity decay of the lithium cobalt oxide material. However, data from examples show that compared with the uncoated lithium cobalt oxide material, the increase in capacity after polymetallic phosphate coating, as well as the improvement in cycle performance, rate performance, and storage performance, are very limited (<10%). In particular, the improved rate performance is still not high and cannot meet the actual needs of power batteries.
[0009] Therefore, there is still a need to find a simple and cost-effective method that can improve both battery performance and safety. Summary of the Invention
[0010] To overcome the limitations of existing technologies, our strategy is to redesign the CEI (Chemical Electrode Injection) on the positive electrode surface, leveraging the synergistic effect of the multifunctional components of the CEI to improve CEI efficiency, thereby comprehensively enhancing the rate performance, cycle performance, and safety performance of the battery. This invention provides a positive electrode sheet for lithium batteries, its preparation method, and its applications. The positive electrode sheet of this invention includes a current collector and a positive electrode material layer located on the surface of the current collector. The positive electrode material layer includes a positive electrode active material, a conductive agent, a binder, a first component, and a second component.
[0011] The first component is selected from LiM12(PO4)3 and Li 1+x Al x Ti2 x (PO4)3, Li 1+x Al x Ge2 x One or more of (PO4)3, wherein M1 is one of Ti, Ge, Zr and Hf, and 0 < x < 0.6; The first component is preferably Li 1.4 Al 0.4 Ti 1.6 (PO4)3, Li 1.4 Al 0.4 Ge 1.6 One of (PO4)3, LiTi2(PO4)3, and LiGe2(PO4)3; The second component is selected from M1O2 and Li 16-4y M1 yAt least one or more combinations of O8, M1P2O7, M2PO4, M32SiO5, M23(PO4)2, and M32SiO4, wherein M2 and M3 are one of Al, Ga, Sc, Y, Ca, Sr, Zn, Si, In, Lu, La, Fe, Cr, and Ge, and wherein 3 <y<4;; The second component is preferably one of InPO4, AlPO4, Al2SiO5, TiO2, and TiP2O7.
[0012] The mixed component consisting of the first component and the second component can be a uniform mixture between the particles of the first component and the particles of the second component, or each primary particle can contain the crystal forms of the first component and the second component.
[0013] The mass ratio of the first component to the positive electrode active material in the positive electrode material layer is w1, where 0 < w1 < 5%, preferably 0.1 < w1 < 3%.
[0014] The mass ratio of the second component to the positive electrode active material in the positive electrode material layer is w2, where 0 < w2 < 5%, preferably 0.1 < w2 < 3%.
[0015] Preferably, the content of the second component is 1 to 20% of that of the first component.
[0016] The particle size of the first component is 10 nm to 10 μm. Preferably, the particle size of the first component is 50 nm to 500 nm.
[0017] The particle size of the second component is 10 nm to 10 μm. Preferably, the particle size of the second component is 50 nm to 500 nm.
[0018] Preferably, based on the weight of the positive electrode material layer as 100%, The content of the positive electrode active material particles is 80~99wt%; The content of the conductive agent is 0.1~8wt%; The content of the adhesive is 0.1~10wt%; The content of the mixed component consisting of the first component and the second component is 0.2~6wt%; Preferably, the positive electrode active material particles are selected from at least one of lithium cobalt oxide positive electrode and its modified materials, NCM ternary positive electrode and its modified materials, NCA ternary positive electrode and its modified materials, lithium nickel manganese oxide positive electrode and its modified materials, lithium-rich positive electrode and its modified materials, and lithium iron phosphate positive electrode and its modified materials. The conductive agent is selected from at least one of Super-P, KS-6, carbon black, carbon nanofibers, carbon nanotubes, acetylene black, or graphene. The binder is selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, homopolymers, copolymers, modified compounds of the above polymers, or mixtures of the above polymers and other polymers or small molecules.
[0019] A second objective of this invention is to provide a method for preparing a positive electrode sheet for lithium batteries, as described in one of the objectives of this invention. The mixed component of the first and second components is incorporated into the positive electrode slurry during the homogenization process. During the preparation of the positive electrode sheet, the mixed component of the first and second components is added and dispersed between the positive electrode active material particles.
[0020] Preferably, the preparation method includes the following steps: Step 1: Mix the first and second components, the positive electrode active material, the conductive additive, the binder, and the solvent evenly to form a slurry; Step 2: Coat the slurry obtained in Step 1 onto the surface of the aluminum current collector to form a positive electrode sheet; Step 3: Dry the positive electrode sheet obtained in Step 2 by blowing air and then by vacuum drying to obtain the final positive electrode sheet.
[0021] Preferably, In step one, The solvent used in the slurry is NMP, wherein the mass ratio of NMP to the cathode material is (2000-10):100.
[0022] In step two, The viscosity of the prepared slurry at 25°C is 3500 mPa·S to 8500 mPa·S.
[0023] In step three, The temperature of the blower drying is 80-180℃, and the time is 10 minutes to 9 hours; the temperature of the vacuum drying is 80-180℃, and the time is 3-100 hours.
[0024] A third objective of this invention is to provide the application of the positive electrode sheet described in one objective of this invention in lithium batteries.
[0025] This invention improves the rate performance, cycle performance, and safety performance of a battery by adding a mixed component of a first component and a second component with a particle size D50 of 0.01-10µm to the positive electrode, in conjunction with a conductive agent and a binder. The technical principle is as follows: First, the first component, possessing lithium-ion conductivity and containing variable-valence transition metal elements (Ti, Ge), is optimal. When this type of component exists between the positive electrode particles, it can form a continuous network, which is beneficial for electrolyte storage and wetting, significantly improving the conductivity of lithium ions within the positive electrode. In particular, the first component is compatible with the positive electrode CEI, improving the mechanical stability of the CEI and forming a superior CEI / electrolyte interface. The second component can suppress unstable, low-ionic-conductivity CEI generated by electrolyte decomposition. The combined use of the first and second components has a synergistic effect, generating a more stable CEI with stronger lithium-ion conductivity that is connected to the lithium-ion conduction network within the positive electrode. This significantly reduces interface resistance and polarization during battery operation, significantly improving the battery's rate performance, surpassing existing technologies. Furthermore, synergistic design can also solve the thermal runaway problem caused by CEI instability, thereby comprehensively improving the rate performance, cycle performance, and safety of the positive electrode. The aforementioned synergistic effect cannot be achieved by adding the first component or the second component alone. If only the first component is added, although it can connect the CEI to the lithium-ion transport network in the electrolyte, battery polarization will still occur if the electrolyte continuously decomposes to produce a CEI with low lithium-ion conductivity. If only the second component is added, the CEI is easily broken because the first component does not improve its mechanical strength, and the electrolyte will decompose at the break point. Therefore, it is often necessary to fully coat the active material with the second component, as disclosed in existing technologies, to suppress electrolyte decomposition, reducing production efficiency. Based on the CEI enhancement by the first component, only a small amount of the second component needs to be mixed in to effectively suppress electrolyte decomposition, which is also an advantage of the synergistic effect. Introducing a mixture of the first and second components into the positive electrode through blending does not change the current mainstream manufacturing processes for positive electrodes, separators, and batteries, offering advantages such as high stability and low cost, making it suitable for large-scale applications.
[0026] Compared with the prior art, the present invention has the following advantages and outstanding effects: The mixed components of the first and second components added to the lithium-ion battery cathode of this invention exhibit high chemical stability. They can be directly incorporated into the cathode active material before cathode preparation, without altering the current mainstream manufacturing processes for cathodes, separators, and batteries. This ensures compatibility with existing mainstream lithium-ion battery cathode manufacturing processes and does not affect the cathode or cell manufacturing processes. It offers advantages such as high stability and low cost, making it suitable for large-scale applications. In contrast, methods of cathode material doping or cathode surface coating require changes to existing cathode material preparation technologies, making it difficult to simultaneously improve discharge specific capacity and rate performance.
[0027] This invention utilizes the first and second components in combination to achieve a synergistic effect, constructing a superior CEI that significantly improves the rate performance of the battery, while also enhancing its cycle performance and safety performance. It is the optimal choice for solving the main existing problems of current power batteries.
[0028] While existing technologies, such as the combination of solid electrolyte and oxide, can improve the ionic conductivity of the cathode, the mixed composition of the first and second components in this invention achieves a stable CEI with faster lithium-ion conduction, making it more suitable for both liquid and solid-state batteries, especially when an electrolyte is present. Existing technologies generally prefer solid electrolytes with high ionic conductivity when using solid electrolyte doping to improve the cathode, while this invention prefers a solid electrolyte compatible with CEI, which can more effectively improve rate performance, as low interfacial transport is a key factor hindering the performance of electrolyte-based batteries. Existing technologies generally use common high-temperature resistant ceramics such as Al2O3 when using oxides to improve the cathode, while this invention prefers compounds that inhibit electrolyte decomposition to improve CEI conductivity and stability, allowing for more precise suppression of thermal runaway. Through the ingenious design of this invention, the synergistic effect of the first and second components is achieved. After optimizing the first component, only a small amount of the second component needs to be mixed in to achieve better results than existing technologies that use the second component to coat the cathode material, thus improving production efficiency.
[0029] The content of the mixed component particles of the first and second components added to the lithium battery positive electrode sheet of the present invention is specially designed. If the content is less than 0.1 wt%, it is difficult to form a complete lithium-ion channel or an effective CEI layer, and the improvement in electrical performance and safety performance is not significant. If the content is greater than 10 wt%, the content of inactive materials in the battery increases, which will reduce the energy density of the battery.
[0030] The positive electrode exhibits excellent rate performance, cycle performance, and safety. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the structure of the lithium battery positive electrode sheet in Example 1; Figure 2 This is a schematic diagram of the lithium battery heavy object impact test fixture of the present invention; Figure 3 This is a schematic diagram of the structure of the lithium battery positive electrode sheet in Example 9. Detailed Implementation The present invention will now be described in detail with reference to the accompanying drawings and embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0032] Example 1 Step 1: Add 1 kg of Li containing the first component 1.4 Al 0.4 Ti 1.6 The mixture of (PO4)3 and the second component AlPO4, 100 kg NCM90, 1 kg SuperP, 1 kg PVDF and 500 kg NMP solvent are mixed evenly to form a slurry; Step 2: Coat the slurry obtained in Step 1 onto the surface of the aluminum current collector to form a positive electrode sheet; Step 3: The electrode obtained in Step 2 is baked at 95℃ for 5 minutes, rolled at 28T, and die-cut to obtain a positive electrode with a layer thickness of 126um. The positive electrode is then vacuum dried at 105℃ for 24 hours to obtain the final positive electrode.
[0033] The content ratio of the first component to the second component is 4:1, and the particle size D50 of the first component and the second component is 200 nm.
[0034] The schematic diagram of the positive electrode sheet for lithium batteries prepared by the above method is shown below. Figure 1 As shown, the electrode includes a positive electrode material layer and a current collector 4. The positive electrode material layer comprises a positive electrode active material 1, a conductive agent, a binder, a first component 2, and a second component 3. The first component 2 and the second component 3 in the positive electrode material layer are dispersed between the particles of the positive electrode active material 1. A soft-pack lithium battery is assembled using this positive electrode sheet and matched with a SiOC650 negative electrode. After the prepared lithium battery undergoes liquid injection, formation, and capacity testing, electrochemical and safety performance tests are performed. Specific electrochemical performance test results are shown in Table 1, and safety performance test results are shown in Table 2.
[0035] The lithium battery electrochemical performance testing methods used in this application are as follows: 1. Cyclic performance testing a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) The battery is discharged at a constant current of 1 C until the discharge termination voltage is reached, then the discharge is stopped and the discharge capacity is recorded; this completes one cycle. c) Repeat steps a and b until the discharge capacity is less than 80% of the discharge capacity in the first cycle, and record the total number of battery cycles at this point.
[0036] 2. Ratio Test a) At 23 ℃±2 ℃, the battery was charged to the charging termination voltage at rates of 0.1 C, 0.2 C, 0.33 C, 1 C, 2 C, and 3 C, respectively, and then discharged to the discharge termination voltage at the same rate. Each cycle was repeated 4 times at the same rate. b) Record the discharge capacity at different discharge rates; c) Calculate the ratio of 2C or 3C discharge capacity to 0.33C discharge capacity, denoted as 2C / 0.33C or 3C / 0.33C, to evaluate rate performance.
[0037] 3. High-temperature cycling a) Charge at a constant current of 1 C at 45 °C until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, then stop charging; b) Let the battery stand at 45 ℃ for 5 h; c) Under high temperature of 45 ℃, the battery is discharged at a constant current of 1 C until the discharge termination voltage is reached, then the discharge is stopped and the discharge capacity is recorded; this completes one cycle. d) Repeat steps a to c until the discharge capacity is less than 80% of the discharge capacity of the first cycle. Record the discharge capacity of the battery and the total number of cycles at this point.
[0038] Lithium-ion battery safety performance testing methods: 1. Overcharge a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) Charge the battery at a constant current of 1 C until thermal runaway occurs, and record the battery voltage value when thermal runaway begins.
[0039] 2. Hot box a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) Place the battery in the test chamber. The test chamber is heated at a rate of 5 °C / min, and the temperature is maintained at 160 °C ± 2 °C for 1 hour. The battery passes if it does not smoke, catch fire, or explode; otherwise, it fails.
[0040] 3. Fall a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) The object is dropped freely from a height of 1m onto a concrete slab; Each side of the pouch battery was dropped once, for a total of six tests. After six tests, the battery is considered to have passed if it does not smoke, catch fire, or explode; otherwise, it is considered to have failed.
[0041] 4. Impact of heavy objects a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) Place battery 8 on the platform surface, and place a metal rod 9 with a diameter of 15.8 mm ± 0.2 mm horizontally on the upper surface of the battery's geometric center. Use a weight of 9.1 kg ± 0.1 kg to freely drop from a height of 610 mm ± 25 mm onto the surface of the battery with the metal rod placed on it, and observe for 6 hours. A schematic diagram of the weight impact test fixture is shown below. Figure 2 5 is the traction rope, 6 is the guide tube, and 7 is the steel impact box (the hinge door is not shown).
[0042] The soft-pack battery is required to undergo impact testing only on its wide side, and each sample must undergo only one impact test. The battery passes if it does not smoke, catch fire, or explode; otherwise, it fails.
[0043] 5. Acupuncture a) Charge at a constant current of 1 C at 23 ℃±2℃ until the charging termination voltage is reached, then switch to constant voltage charging until the charging current rate drops to 0.05 C, stop charging, and let stand for 1 h. b) Using a φ8mm high-temperature resistant steel needle (with a cone angle of 45° at the needle tip, and a smooth surface free of rust, oxide layer and oil), insert the needle at a speed of 25 mm / s from a direction perpendicular to the battery plate, with the insertion point being the geometric center of the pierced surface, and the steel needle remaining in the battery. c) Observe for 1 hour; The battery passes if it does not smoke, catch fire, or explode; otherwise, it fails.
[0044] Example 2 The first component is replaced with Li. 1.4 Al 0.4 Ge 1.6 (PO4)3 was used, with the positive electrode active material replaced by NCM83. The battery structure was NCM83||SiOC650, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0045] Example 3 The first component was replaced with LiTi2(PO4)3, the second component with Ti3(PO4)4, the positive electrode active material with NCM83, and the negative electrode with SiOC450. The battery structure was NCM83||SiO450, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0046] Example 4 The first component was replaced with LiGe2(PO4)3, the second component with Ca3(PO4)3, the positive electrode active material with LCO, and the negative electrode with SiOC450. The battery structure was LCO||SiO450, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0047] Example 5 The second component was replaced with LaPO4, the positive electrode active material was replaced with LFP, and the negative electrode was replaced with graphite. The battery structure was LFP||graphite, and other parameters were the same as in Example 1. The lithium battery prepared above was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0048] Example 6 The first component is replaced with Li. 1.4 Al 0.4 Ge 1.6 The second component of the lithium battery was replaced with FePO4, the positive electrode active material was replaced with NCM83, and the negative electrode was replaced with graphite. The battery structure was NCM83||graphite, and other parameters were the same as in Example 1. The prepared lithium battery underwent electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0049] Example 7 The particle size D50 of both the first and second components was replaced with 50 nm, and other parameters were the same as in Example 1. The prepared lithium battery was then subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0050] Example 8 The particle size D50 of both the first and second components was replaced with 500 nm, and other parameters were the same as in Example 1. The prepared lithium battery was then subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0051] Example 9 The first component is replaced with Li. 1.4 Al 0.4 Ti 1.6 (PO4)3, the second component is replaced with AlPO4, and the total amount of the mixed component consisting of the first and second components is replaced with 0.5 kg. Each primary particle of the mixed component contains particles of both the first and second component crystal forms, and the particle size D50 of the primary particles of the mixed component is 200 nm. The mixing form is as follows: Figure 3 As shown, 1 represents the positive electrode active material, 10 represents the mixture of the first and second components in the same particle, and 4 represents the current collector. Other parameters are the same as in Example 1. The lithium battery prepared above was subjected to steps such as liquid injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0052] Example 10 The first component is replaced with Li. 1.4 Al 0.4 Ti 1.6 (PO4)3, the second component is replaced with AlPO4, and the total amount of the mixed components consisting of the first and second components is replaced with 5 kg, with other parameters the same as in Example 9; the lithium battery prepared above is subjected to steps such as liquid injection, formation, and capacity testing, and then electrochemical and safety performance tests are performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0053] Comparative Example 1 The first component and the second component were omitted, and other parameters were the same as in Example 1. The prepared lithium batteries were subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium batteries are shown in Table 1, and the safety performance test results are shown in Table 2.
[0054] Comparative Example 2 The first and second components were omitted, and the positive electrode active material was replaced with NCM83. The battery structure was NCM83||SiOC650, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0055] Comparative Example 3 The first and second components were omitted. The positive electrode active material was replaced with NCM83, and the negative electrode was SiOC450. The battery structure was NCM83||SiOC450, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0056] Comparative Example 4 The first and second components were omitted. The positive electrode active material was replaced with LCO, and the negative electrode was SiOC450. The battery structure was LCO||SiOC450, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0057] Comparative Example 5 The first and second components were omitted. The positive electrode active material was replaced with LFP, and the negative electrode was graphite. The battery structure was LFP||graphite, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0058] Comparative Example 6 The first and second components were omitted. The positive electrode active material was replaced with NCM83, and the negative electrode was graphite. The battery structure was NCM83||graphite, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0059] Comparative Example 7 The mixed component consisting of the first and second components was replaced with 1 kg of Al2O3, with other parameters remaining the same as in Example 1. The prepared lithium battery underwent electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0060] Comparative Example 8 The mixed component consisting of the first and second components was replaced with 1 kg of ZnO, and the positive electrode active material was replaced with NCM83. The battery structure was NCM83||SiOC650, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0061] Comparative Example 9 The mixed component consisting of the first and second components was replaced with 1 kg of Li. 1.4 Al 0.4 Ti 1.6 The positive electrode active material was replaced with NCM83, and the negative electrode was replaced with SiOC450. The battery structure was NCM83||SiOC450, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0062] Comparative Example 10 The mixed component consisting of the first and second components was replaced with 1 kg of AlPO4, the positive electrode active material was replaced with LCO, and the negative electrode was replaced with SiOC450. The battery structure was LCO||SiOC450, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, and then electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0063] Comparative Example 11 The mixed component consisting of the first and second components was replaced with 1 kg of Li. 0.5 La 0.5 TiO3 was used, with the positive electrode active material replaced by LFP and the negative electrode replaced by graphite. The battery structure was LFP||graphite, and other parameters were the same as in Example 1. The prepared lithium battery was subjected to electrolyte injection, formation, and capacity testing, followed by electrochemical and safety performance tests. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0064] Comparative Example 12 The mixed component consisting of the first and second components was replaced with 1 kg of Li7La3Zr2O. 12The positive electrode active material was replaced with NCM83, and the negative electrode was replaced with graphite. The battery structure was NCM83||graphite, and other parameters were the same as in Example 1. After the prepared lithium battery underwent liquid injection, formation, and capacity testing, electrochemical and safety performance tests were performed. The specific electrochemical performance test results of the prepared lithium battery are shown in Table 1, and the safety performance test results are shown in Table 2.
[0065] Table 1 shows the electrochemical performance data of the examples.
[0066] Table 1
[0067] Table 2 shows the safety performance data of the embodiments.
[0068] Table 2
[0069] As shown in Tables 1 and 2, the mixed composition of simultaneously incorporating the first and second components into the positive electrode can significantly improve the rate performance, cycle performance, and safety performance of the battery. A comparison between Example 3 and Comparative Example 9 reveals that the mixed composition of simultaneously incorporating the first and second components into the positive electrode is far more effective in improving the rate performance, cycle performance, and safety performance than simply incorporating a high-lithium-ion-conductivity solid electrolyte into the positive electrode. This is because constructing an efficient CEI and CEI / electrolyte interface is crucial for improving the electrical and safety performance of both liquid and solid-state batteries. A comparison between Example 4 and Comparative Example 10 shows that the mixed composition of simultaneously incorporating the first and second components into the positive electrode is far more effective in improving the rate performance, cycle performance, and safety performance than simply incorporating phosphate to inhibit electrolyte decomposition into the positive electrode. The difference in improving battery electrical performance between the two examples is particularly significant. This is because constructing a high-lithium-ion-conductivity CEI and connecting the CEI with the lithium-conducting network in the electrolyte is important, which cannot be achieved by simply adding phosphate to the positive electrode. A comparison of Example 1 with Examples 7 and 8 shows that the mixed component of the first and second components has an optimal particle size. Optimizing the particle size can improve the rate performance and cycle performance of the battery. If the particle size is too small, the mixed component of the first and second components is prone to agglomeration; if the particle size is too large, the mixed component of the first and second components cannot fully contact the surface of the active material particles. Both excessively small and large particle sizes are not conducive to the construction of a stable CEI. A comparison of Example 1 with Comparative Examples 9 and 10 shows that there is an optimal ratio of the added amount of the mixed component of the first and second components. If the added amount is too low, it cannot fully improve the rate performance and safety performance of the battery; if the added amount is too high, it is not conducive to achieving higher rate performance. This may be because if the mixed component of the first and second components is too high, particle aggregation will form a region with low lithium-ion conductivity.
[0070] It is understood that the above embodiments are merely exemplary implementations used to illustrate the principles of the present invention, and the present invention is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A lithium battery positive electrode sheet, the positive electrode sheet comprising a positive electrode material layer, the positive electrode material layer comprising a positive electrode active material, a conductive agent, a binder, a first component, and a second component, characterized in that: The first component is selected from LiM12(PO4)3 and Li 1+x Al x Ti2 x (PO4)3, Li 1+x Al x Ge2 x One or more of (PO4)3, wherein M1 is selected from one of Ti, Ge, Zr and Hf, and 0 < x < 0.6; The second component is selected from Li 16-4y M1 y At least one or more combinations of O8, M1P2O7, M2PO4, M32SiO5, M23(PO4)2, and M32SiO4, wherein M1 is selected from Ti, Ge, Zr, and Hf; M2 is selected from Sc, Y, Ca, Sr, Zn, Si, Lu, La, Fe, Cr, and Ge; and M3 is selected from Al, Ga, Sc, Y, Ca, Sr, Zn, Si, In, Lu, La, Fe, Cr, and Ge, wherein 3 <y<4; The mass ratio of the first component to the positive electrode active material in the positive electrode material layer is w1, where 0.1 < w1 < 5%. The mass ratio of the second component to the positive electrode active material is w2, where 0.1 < w2 < 5%. The first and second components in the positive electrode material layer are dispersed between the particles of the positive electrode active material; The particle size of the first component is 50nm-500nm; the particle size of the second component is 50nm-500nm.
2. The lithium battery positive electrode sheet according to claim 1, characterized in that: The first component is Li 1.4 Al 0.4 Ti 1.6 (PO4)3, Li 1.4 Al 0.4 Ge 1.6 One of (PO4)3, LiTi2(PO4)3, and LiGe2(PO4)3; And / or, the second component is one of Al2SiO5, FePO4, LaPO4, Ca3(PO4)3, Ti3(PO4)4, and TiP2O7; And / or, the mixed component consisting of the first component and the second component is a uniform mixture between the particles of the first component and the particles of the second component, or each primary particle contains the crystal form of the first component and the crystal form of the second component.
3. The lithium battery positive electrode sheet according to claim 1, characterized in that: 0.1<w1<3%; 0.1<w2<3%。 4. The lithium battery positive electrode sheet according to claim 1, characterized in that: The positive electrode active material includes at least one of lithium cobalt oxide and its modified materials, NCM ternary cathode and its modified materials, NCA ternary cathode and its modified materials, lithium nickel manganese oxide cathode and its modified materials, lithium-rich cathode and its modified materials, and lithium iron phosphate and its modified materials.
5. A method for preparing a lithium battery positive electrode sheet according to any one of claims 1-4, characterized in that: The preparation method includes the following steps. Step 1: Mix the first and second components, the positive electrode active material, the conductive additive, the binder, and the solvent evenly to form a slurry; Step 2: Coat the slurry obtained in Step 1 onto the surface of the aluminum current collector to form a positive electrode sheet; Step 3: Dry the positive electrode sheet obtained in Step 2 by blowing air and then by vacuum drying to obtain the final positive electrode sheet.
6. A lithium battery cell, characterized in that: The lithium battery cell includes a positive electrode, a negative electrode, a separator, an electrolyte, and a casing, wherein the positive electrode is the lithium battery positive electrode as described in any one of claims 1-4.
Citation Information
Patent Citations
A quasi-solid-state electrolyte, its preparation method and application
CN108365260B
Strontium-doped ternary lithium ion battery positive electrode material, and preparation method and application thereof
CN113224287A
A phosphate-coated lithium cobalt oxide cathode material and its preparation method
CN113346066B
Positive pole piece containing solid electrolyte, and preparation method and application thereof
CN113707880A
Positive electrode material and preparation and application thereof
CN113809280A